2007
DOI: 10.1063/1.2743963
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of water surrounding the poly(methacrylic acid): A molecular dynamics study

Abstract: All-atom molecular dynamics simulations are used to study a single chain of poly(methacrylic acid) in aqueous solutions at various degrees of charge density. Through a combination of analysis on the radial distribution functions of water and snapshots of the equilibrated structure, we observe that local arrangements of water molecules, surrounding the functional groups of COO- and COOH in the chain, behave differently and correlated well to the resulting chain conformation behavior. In general, due to strong a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 51 publications
4
37
0
Order By: Relevance
“…76,77 If present, the waters within this array will exchange with waters in the bulk solvent, but at some rate much slower than the bulk exchange rate. 94 If this picture is accurate, the solvation region around sulfur will include slow-exchange water molecules that can contribute some back-scattering intensity to the sulfur K-edge spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…76,77 If present, the waters within this array will exchange with waters in the bulk solvent, but at some rate much slower than the bulk exchange rate. 94 If this picture is accurate, the solvation region around sulfur will include slow-exchange water molecules that can contribute some back-scattering intensity to the sulfur K-edge spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Similar water molecule networks have been reported for other dissolved aqueous amino acids. [73][74][75][76][77] Such a network would constitute an extended stable shell of water molecules about cysteine. Any durably located bridging network of hydrogen-bonded water molecules with a S Cys -O w1 -O w2 angle of 150…”
Section: B Mxan Fitting Experimentsmentioning
confidence: 99%
“…behavior of salts and the dynamics of water [27][28][29][30][31][32][33]. For example, Molnar [27] studied the mechanism of ''like-charge attraction'' by the fully atomistic molecular dynamics simulations and found that the interaction of calcium ions with single chains of poly(acrylic acid)(PAA) strongly influenced the original sodium ion distribution and shielded polyanions from approaching each other, which was contrary to the assumption that precipitation is initially induced by intermolecular Ca 2+ bridging.…”
Section: Introductionmentioning
confidence: 88%
“…Various all-atom computer simulations have been used to study the interaction of salts ions with the -COO À functional groups of the polycarboxylate-type superplasticizers and found that Ca 2+ ions bridging was responsible for the conformational collapse [28,31]. However, only single polyelectrolyte chain in salt solution was usually selected as the model, and therefore only intramolecular Ca 2+ bridging was observed.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation